Redescription and Range Extension of Microhyla sholigari Dutta & Ray (Amphibia: Anura: Microhylidae) from South West India - Seshadri, Kadaba Shamanna; Priti, H.; Ravikanth, G.; Vidisha, M. K.; Vineeth, K. K.; Singal, Ramit; Sarma, R. R.; Aravind, N. A.; Gururaja, Kotambylu Vasudeva (Zootaxa, 2016)
Microhyla sholigari is an endangered frog described in the year 2000. The original description was based on non-adult types and lacked information on several morphological characters, call structure, genetic material and photographs of the animal in life. The absence of such information posed challenges in field identification of this species. Since the original description, there is one other reported sighting of this species from Kerala in 2001. We encountered specimens that we confer to this species based on morphological similarity to the subadult holotype, from several new localities within and outside the Western Ghats of Karnataka. We here redescribe the species based on additional adult vouchers, provide molecular data, describe the advertisement call and report a range extension. Based on its current distribution, we assess the threat status of the species and suggest listing it as Least Concern according to IUCN Red List criteria. Our paper bridges an important gap in the knowledge of the genus Microhyla in India and highlights the importance of systematic surveys in documenting and understanding amphibian diversity in the region.